«Methodological guidelines for business education development in Ukraine» - Maikovska, V. (Problems of Engineer-Pedagogical Education, 2022)
The publication examines the methodological principles of forming entrepreneurial competence of future professionals in the system of vocational training and practical aspects of business education in Ukraine and the world, seeks to guide the development of business education in the national education system. It is noted that with the development of the knowledge economy, the labor market needs to have in the structure of the personality of a specialist entrepreneurial competence as a new priority of professional qualifications, the responsibility for the formation of which rests with education. An analysis of theoretical works of domestic and foreign experts, in which business education is considered as an informal, alternative, fully focused on the conditions of the knowledge economy area of training, which - unlike vocational education - connects education and practical entrepreneurship. It is established that the world business education fulfills the socio-economic order of modern society to train professionals who can successfully work in the knowledge economy in eleven subject areas of life of each market participant. Two leading models of business education - German and American - have been identified, which demonstrate their success in the market environment and with some changes may be prototypes for building a system of national business education. It is emphasized that the socio-economic significance of Ukrainian business education is manifested in the formation in accordance with the needs of a market society, a fundamentally new system of continuing education; creating opportunities for the development of individual educational trajectories; introduction of the competence approach in the educational process, strengthening the practical orientation of economic training of future specialists. The experience of searching for methodological bases of formation of entrepreneurial competence of future specialists in the context of their professional training at philosophical, general scientific, concrete-scientific and technological levels with the use of appropriate scientific approaches and principles is presented.